Identifying the indicators of the problems of couples seeking a divorce in Torkaman city - Jomenia, Sakineh; Nazari, Ali Mohammad; Soliemanian, Ali Akbar (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The present research was written to identify the problems of couples of Torkaman city from the perspective of Torkaman couples. Methods: This research was a qualitative content analysis method. The statistical population of this study included all Torkaman couples seeking divorce referred to the counseling center by the judiciary for peace and reconciliation. Twenty couples were selected based on purposive sampling and saturation criteria and participated in the study. An in-depth semi-structured interview method was used to collect the data. Results: After analyzing the data, 4 main categories of marital inefficiency, individual inefficiency, underlying conditions, and cultural conditions were obtained. Marital inefficiency included 14 sub-categories (couple’s reaction in the event of a dispute, dysfunctional relationship, lack of alignment and coordination with each other, lack of sexual intimacy, infidelity, deprivation of love, disregard for kinship and friendship, failure to play marital roles, and destructive role of families, reaction of families when there is a dispute, lack of transparency and honesty in the relationship, inefficient life stages, negative attitude towards the future of the relationship, inattention and difference in religious attitude). Individual inefficiency included 1 sub-category (effective personality traits in divorce). Underlying conditions included 2 sub-categories (Improper formation of marriage, social factors affecting divorce) and cultural conditions included 1 sub-category (cultural factors affecting divorce). Conclusion: According to the findings, it can be concluded that there will be effective steps taken to improve marital life by developing an educational package based on the problems of the couples in Torkaman city.